Awareness of HPV and HPV vaccination in undergraduate students in the North West region of Turkey: Near future outlook - Gulden Aynaci; Zuhal Guksu (Journal of Infection in Developing Countries)
Introduction: Cervical cancer is the second most common cancer affecting women in the world. Human papillomavirus (HPV) is the most common sexually transmitted infection worldwide. The aim of this study was to evaluate the awareness about HPV, risk perception, cervical cancer, and HPV vaccines.